Preliminary investigation on the effects of primary airflow to coal particle distribution in coal-fired boilers - Noor N.A.W.M.; Hassan H.; Hashim M.F.; Hasini H.; Munisamy K.M. (Institute of Physics Publishing, 2023)
Air; Boilers; Coal; Coal combustion; Combustion; Computational fluid dynamics; Fluid dynamics; Fluid mechanics; Fossil fuel power plants; Grinding mills; Particle size; Air flow-rate; CFD simulations; Coal particle size; Coal particles; Coal-fired power plant; Combustion efficiencies; Performance problems; primary airflow; Coal fired boilers